Implementasi Kegiatan Role Play Terhadap Perkembangan Sosial Emosional Anak Usia 5-6 Tahun - Ariyanti, Lilik; Farida, Siti; Janah, Laila Nurul; Andawiyah, Rofiatul (Generasi Emas : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to describe the implementation of role-playing activities in promoting the social-emotional development of children aged 5–6 years. A qualitative descriptive approach was employed at RA Asy Syuhada'. The participants consisted of 15 Group B children and their classroom teacher. Data were collected through observations, interviews, and documentation and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that role-playing activities effectively promote children's social-emotional development, particularly in communication skills, self-confidence, cooperation, empathy, and peer interaction. Among these indicators, self-confidence and social communication skills emerged as the most prominent improvements, as children became more confident in expressing their ideas and interacting with their peers during learning activities. This study also demonstrates that role-playing provides meaningful and contextual learning experiences by actively engaging children in authentic social situations. Therefore, role-playing can be considered an effective learning strategy for supporting children's social-emotional development in early childhood education.